Physiological and biochemical differences in diapause and non-diapause pupae of Sericinus montelus (Lepidoptera: Papilionidae) - Xiao, Quan-Hong; He, Zhe; Wu, Rong-Wei; Zhu, Dao-Hong (Frontiers in Physiology, 2022)
The swallowtail butterfly, Sericinus montelus Gray, is endemic to East Asia, has high ornamental value but faces an increased risk of extinction. To understand the overwintering strategies of this species, the dynamic changes in supercooling point (SCP) and water and biochemical contents of diapause-destined and non-diapause S. montelus pupae were investigated. The SCP of laboratory-reared diapause pupae was as low as –26°C compared to –24°C in diapause pupae in the field. Although there was no significant difference in total water content between diapause-destined and non-diapause pupae, the free water of diapause-destined pupae was significantly lower, and the bound water was significantly higher, than that of non-diapause pupae. Lipid, glycogen, and protein contents of diapause-destined pupae showed a downward trend, whereas the total sugar content showed the opposite trend after pupation. The glycogen content decreased rapidly during the initial stage of pupation, whereas the lipid content decreased significantly after 30 days of pupation, suggesting that diapause-destined pupae deplete glycogen stores during the pre-diapause period and then switch to using lipids during the diapause maintenance phase. Trehalose levels in diapause-destined pupae increased significantly and remained high after pupation. Meanwhile, the trehalose content of overwintering pupae during the diapause maintenance period was significantly higher than that of diapause termination pupae in the field. These results suggest that trehalose is the main cryoprotectant for overwintering pupae. Thus, diapausing S. montelus pupae appear to be freeze avoidant, accumulate trehalose as a cryoprotectant, and reduce the free water content to decrease the SCP, enhancing their cold tolerance.